(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the Worlds, with whom he began his book, and with whom they called upon the people of His Paradise, and may God’s blessings be upon our Prophet and intercessor, Muhammad, and his pure and pure family and his noble and noble companions. The method is the backbone of teaching, and a major reason for its success and how to understand the scientific material. Therefore, the research tagged (Methods of Teaching the Noble Prophet’s Hadith) is a research work that adds to knowledge an asset from the principles of teaching in general, and teaching the Prophet’s hadith is the second source in Islamic legislation in a way In writing his research, the researcher referred to references, sources, and general and special studies in teaching and its methods, as well as Islamic education books, including the sources of hadith and biography, and Islamic education books and teaching, which are based in their approach on the most important source of legislation (the Prophet’s hadith), and the research plan was It includes three topics according to the following titles:The first topic: definition of the research (the research problem, its importance, objectives and terminology)The first requirement: the research problem and its importanceThe second requirement: the aim of the research and its terminologyThe second topic: the importance of teaching the hadith of the Prophet and its objectivesThe first requirement: the importance of teaching hadithThe second requirement: the objectives of teaching hadithThe third topic: Methods of teaching the Noble Prophet’s Hadith and its steps)The first requirement: methods of teaching the hadith of the ProphetThe second requirement: the steps of teaching the hadith of the Prophet